Apolipoprotein A-I mimetic peptides (ApoAI MP) improve oxidative stress and inflammatory responses in Parkinson’s disease mice - Jiang, Hongfang; Bai, Xue (Frontiers in Pharmacology, 2022)
Purpose: Parkinson’s disease (PD) is closely associated with oxidative stress and inflammatory situation. Apolipoprotein A-I mimetic peptides (ApoAI MP) have antioxidant and anti-inflammatory properties. We aimed to study the therapeutic effect of ApoAI MP on PD mice, and to explore the related mechanisms. Methods: PD mice were induced by using 1-methyl-4-phenyl-1,2,3,6-tetrathydropyridine (MPTP). The model mice were treated with different concentrations of ApoAI MP. The open-field behavioral test assesses the total distance moved, the rest time, and the number of crossings and Rota-rod was used to evaluate motor coordination. Oxidative stress was identified by measuring the levels of superoxide dismutase (SOD), catalase (CAT), glutathionperoxidase (GSH-Px), malondialdehyde, ROS and H2O2. Inflammatory situation was analyzed by measuring the levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6). Meanwhile, the scavenging activities of ApoAI MP for ABTS, DPPH, hydroxyl radical and superoxide anion, and the effects of the peptide on neurotransmitters were evaluated. Results: PD model establishment increased oxidative stress and inflammatory status by increasing the concentrations of ROS and H2O2 production, and the levels of TNF-α, IL-1β and IL-6 (p < 0.05). ApoAI MP intervention improved PD symptoms by reducing the total moved distance and the number of passes (p < 0.01), and the falling times from Rota-rod, and increasing rest time (p < 0.05). ApoAI MP increased antioxidant properties by increasing the activities of SOD, CAT and GSH-Px, and reducing MDA concentration (p < 0.05). ApoAI MP addition reduced oxidative stress by scavenging ABTS, DPPH, hydroxyl radicals and superoxide anion and reducing the concentrations of ROS and H2O2 production (p < 0.05). ApoAI MP treatment increased anti-inflammatory capacities by reducing the concentrations of TNF-α, IL-1β and IL-6 (p < 0.05). HPLC analysis showed that the peptide treatment improved neurotransmitters. Conclusion: ApoAI MP can improve the behavioral performance of PD mice by improving antioxidant and anti-inflammatory capacities.